CAUSALITY GRANGGER BETWEEN GOLD AND INDONESIA SHARIA INDEX - Andri Faisal; Kampono Imam Yulianto (Jurnal Ekonomi, 2022)
Gold has long been a very profitable investment. Gold protects from all financial risks due to even a bad economic situation or is also called a safe haven. In addition, there is stock investment which is an alternative to existing investments. In some countries, shares provide very large profits for shareholders. During a booming economy, stocks are the next choice after gold. On the other hand, if the economy is difficult, investors will turn to gold. There is a connection between the two investments. It could be gold that affects the stock price because with the low price of gold all investors will look for alternatives to gold investment, namely stock investment. At a certain time, stock investment will provide more results. There is a need to investigate the relationship between gold and Islamic stocks and Islamic stocks and gold. If you know the two directions of the relationship, it will be easy to predict the two investments. As for the two data through differencing so that the data becomes stationary. By using Grangger causality will test the existence of a relationship between the two. The results of two variables do not have a significant relationship. Neither gold nor Islamic stocks affect each other.